STRATEGI PENYULUHAN DAN PARTISIPASI MASYARAKAT DI TAMAN NASIONAL KEPULAUAN TOGEAN - Muhd Nur Sangadji (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
The aim of this research was to determine the  influence of community  participation and extension strategy to  increase the community participation on the  management of the Togean Island National Park. The research was conducted  in the Togean Island National Park in Central Sulawesi on September 2011. Five variables were used to measure  the community participation using Structural Equation Model (SEM) and  LISEREL 8.30 sofware. Those variables were internal characteristics,  extension proccess,  external factors, community capacity and community participation. The results of the research showed that extension proccess have a significant effect on the community capacity.  It also showed that the community capacity has a significant effect on the community participation on management of Togean Island National Park. The strategic implementation that can be used to increase the community participation is to  improve the process of extension. This strategy should be supported by willingness of government to consistently applied the concept of collaborative management of National Park  at the local level. Key Words : Extension strategy and Participatory aproach.